THU0203 Baricitinib Targets The Type I IFN/STAT-Medicated Activities of Human T Cells and Dendritic Cells. (15th July 2016) - Kubo, S.; Nakayamada, S.; Nakano, K.; Tanaka, Y.
Abstract : Background: The JAK/STAT pathway is a potent therapeutic target in autoimmune diseases. We previously reported that tofacitinib, a JAK1/3 inhibitor, suppressed pro-inflammatory cytokine production and co-stimulatory molecule expression on dendritic cells via suppression of IFN/STAT signal and directly inhibited lymphocyte proliferation. To date, baricitinib, a JAK1/2 inhibitor, has shown dramatic effect in the treatment of rheumatoid arthritis. However, the exact targets of the cells and cellular signaling by baricitinib remain unclear. Objectives: To elucidate the mechanisms of action of baricitinib, we shed light on the JAK/STAT signal on human T cells and dendritic cells. Methods: The effects of baricitinib and tofacitinib on the human CD4 + T cells proliferation, phosphorylation of STAT, the maturation of human monocyte-derived dendritic cells, and the cytokine production of human plasmacytoid dendritic cells were investigated. Results: Human T cells were proliferated after stimulation with anti-CD3 and anti-CD28 antibody. However, the T cell proliferation was significantly suppressed by the addition of baricitinib in a dose dependent manner. Both IFN-α and IL-6 induced phosphorylation of STAT1, STAT3 and STAT4 in human T cells. IL-12 induced phosphorylation of STAT4. IL-21 induced phosphorylation of STAT3 and STAT4. However, IL-23 did not induce the phosphorylation of STAT. Baricitinib, as well as tofacitinib, inhibited the phosphorylation of STAT1, STAT3 and STAT4 induced by IFN-α, IL-6 and IL-21. Interestingly, the inhibition effect of baricitinib on phosphorylation of STAT4 which was induced by IFN-α was stronger than that of tofacitinib. On the other hand, CD80/CD86 and HLA-DR of human monocyte-derived dendritic cells (MoDCs) were significantly induced at 48 hour after lipopolysaccharide (LPS) stimulation. The CD80/CD86 expression in MoDCs was suppressed by the addition of baricitinib in a concentration-dependent manner, while the expression of HLA-DR was not affected. The induction of CD80/CD86 expression by LPS stimulation was also suppressed by tofacitinib. Moreover, the expression of CD80/CD86 which was induced by LPS was completely suppressed by the addition of an anti-type-I IFN receptor antibody. Baricitinib and tofacitinib suppressed the production of type-I IFN from plasmacytoid dendritic cells; however, it did not affect TNF-α production. Conclusions: Tofacitinib and baricitinib inhibited not only lymphocyte proliferation but also T cell stimulatory capacity of human dendritic cells through suppression of type-I IFN and STATs signaling. Baricitinib characteristically inhibited the activation of IFN/STAT4 signal stronger than that of tofacitinib. Taken together, the different mode of action among JAK inhibitors may affect the clinical effects in patients not only with rheumatoid arthritis but other immune-mediated diseases. Disclosure of Interest: S. Kubo: None declared, S. Nakayamada: None declared, K. Nakano: None declared, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Chugai, Astellas, Eisai, Taisho-Toyama, Kyowa-Kirin, Abbvie, Bristol-Myers, Consultant for: Abbvie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, Eli Lilly, GlaxoSmithKline, UCB, Teijin, MSD, Santen